Analysis of risks in critical infrastructure networks - Chong, Gary Hong Chang (2015)
The three most common terms found in the studies of risk, namely ‘risk management’, ’risk analysis’ and ’vulnerability’ was to be determined if they have similar meanings. An effective risk management team is crucial for the long term outlook of a company. Thus, only through the use of risk analyses can proper decision making take place. This is made possible through the use of various methodologies like risk modeling, coarse risk analysis, failure modes and effects analysis (FMEA), fault tree analysis and bow-tie diagrams. Besides this, the inclusion and determination of vulnerability has to be considered when analyzing risk. Quantitative approaches to vulnerability include the use of the United Nations development programme and the use of Disaster Risk Index (Peduzzi, 2006) to analyze risk across countries. Qualitative approaches, however, are more useful on a community level as they have the capability to know more about how a society manage hazard. This can be through drawings, dialogues and the use of timelines.